Documentation of the Bantu language Mpiemo of the Central African Republic (A86c) - Thornell, Christina (University of Gothenburg, 2014)
The overall aim of the study has been to document and preserve the minority language Mpiemo as well as to analyse it from a linguistic perspective. The language is spoken in some regions of the Central African Republic and Cameroon. The language is classified as A86c according to the Guthrie system and has approximately 29,000 speakers. When the project started there was a translation of the four gospels with a French-based orthography, but no other texts. The documentation has spanned several projects from 1998 onwards and has resulted in, amongst other things, a number of articles on Mpiemo phonetics, phonology, morphology as well as the publication of recorded speech together with transcripts and annotations and texts about the local wild plant life.

Purpose:

The purpose of the project has been to document and linguistically analyse the Central African language Mpiemo by means of varying subprojects.

Trilingual word list Mpiemo-French-English containing roughly 1,900 words and grammatical information like word class and noun class. The word list is an updated and extended version of the unpublished lists put together by Laurent Wanabetsina, Keith Beavon and Nkali Lazaro Mbaro (1986) and Lydia Lundström (197?). For the updates a number of native Mpiemo speakers, among others Abel Mabessimo and Zacharie Metekouli, have been consulted. They spoke the Mpiakoumbo and Kwabili dialects. The words in this list are phonological transcriptions. The dataset consists of the word list in an Excel file and sound recordings of the words.

Studiens övergripande syfte har varit att dokumentera och bevara minoritetsspråket mpiemo samt att analysera det ur ett lingvistiskt perspektiv. Språket talas i delar av Centralafrikanska republiken och Kamerun. Språket klassificeras som A86c enligt Guthrie-systemet och har runt 29 000 talare. Då projektet började fanns en översättning av de fyra evangelierna med fransk-baserad stavning men inga andra texter. Dokumentationen har sträckt sig över flera projekt från 1998 och framåt och har bland annat resulterat i en rad artiklar om mpiemos fonetik, fonologi, morfologi och även publicering av inspelat tal med transkriptioner och annoteringar och texter om vilda växter i området.

Syfte:

Syftet med projektet har varit att genom olika delprojekt dokumentera det centralafrikanska bantuspråket mpiemo och göra lingvistiska analyser på materialet.

Trespråkig ordlista mpiemo-franska-engelska innehållande ca 1900 ord som även innehåller grammatisk information som ordklasstillhörighet och för substantiven klasstillhörighet. Ordlistan är en uppdatering och utvidgning av de opublicerade ordlistorna sammanställda av Laurent Wanabetsina, Keith Beavon och Nkali Lazaro Mbaro (1986) och Lydia Lundström (197?). För uppdateringen har ett antal modersmålstalande mpiemotalare, bl.a. Abel Mabessimo och Zacharie Metekouli, konsulterats. De talade dialekterna mpiakoumbo och kwabili. Orden i den aktuella ordlistan har fonologisk form. Datasetet innehåller ordlistan i en excelfil och ljudfiler till orden.
Dokumentation av det centralafrikanska bantuspråket mpiemo (A86c)
Keywords: minority languages; minoritetsspråk; folklore; folksagor; translation; översättning; linguistics; lingvistik; linguistic analysis; lingvistisk analys; Mpiemo; mpiemo; Bantu languages; bantuspråk; A86c; A86c; endangered languages; hotade språk; word list; ordlista; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Studies of Specific Languages; Studier av enskilda språk